SOSIALISASI POLA DIET SEHAT PADA PENDERITA DIABETES MELITUS RT 16 RW 04 KELURAHAN RAWA BUAYA - Saharudin Nisi (Jurnal Pengabdian Masyarakat Kesosi, 2022)
DM patients who have good knowledge will have awareness of their disease. The patient will participate in the management of the disease thereby reducing the burden on health care providers and achieving optimal disease control and minimizing the occurrence of complications. Lack of knowledge and awareness in DM patients will also affect the ability of DM patients to handle their disease, thereby increasing the risk of DM complications. This community service aims to socialize the diabetes diet pattern in order to minimize the increase in blood sugar levels to avoid complications of injury and DFU. Respondents in this activity were people with diabetes mellitus who experienced problems in controlling blood sugar levels. Evaluation of this activity was carried out by giving post test questions to the respondents, and the results were very good. Respondents can know and answer questions correctly, especially in terms of menu selection, time and frequency of eating in people with diabetes mellitus. After the community service activities are completed which are carried out in the form of counseling, it can be concluded that respondents who take part in the activities can understand about healthy diet patterns for people with diabetes mellitus.